Anticompetitive Effects of Common Ownership - AZAR, JOSÉ; SCHMALZ, MARTIN C.; TECU, ISABEL (Journal of Finance, 2018)
ABSTRACT Many natural competitors are jointly held by a small set of large institutional investors. In the U.S. airline industry, taking common ownership into account implies increases in market concentration that are 10 times larger than what is “presumed likely to enhance market power” by antitrust authorities. Within‐route changes in common ownership concentration robustly correlate with route‐level changes in ticket prices, even when we only use variation in ownership due to the combination of two large asset managers. We conclude that a hidden social cost—reduced product market competition—accompanies the private benefits of diversification and good governance.